2012
DOI: 10.4236/ojsst.2012.21002
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation on the Dynamic Stability of Scissor Lift

Abstract: The tip-over of scissor lifts in operation has frequently resulted in the death and/or severe injuries of workers. The objective of this study is to enhance the understanding of its major mechanisms and factors influencing scissor lift stability. Both experimental and modeling approaches were used in this study. Two series of experiments were performed under possible tip-over scenarios: curb impact and pothole depression. Based on the dynamic characteristics identified from the experimental results, a lumped-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…1 shows a flowchart that outlines the theoretical basis and major activities of this study. Similar to the forward dynamic approach, the inverse dynamic approach can be applied to any model with linear or nonlinear dynamic properties [614]. The human body or segment has some nonlinear properties.…”
Section: Basic Theory and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…1 shows a flowchart that outlines the theoretical basis and major activities of this study. Similar to the forward dynamic approach, the inverse dynamic approach can be applied to any model with linear or nonlinear dynamic properties [614]. The human body or segment has some nonlinear properties.…”
Section: Basic Theory and Methodologymentioning
confidence: 99%
“…The results can be used to replace the linear stiffness and damping properties in the model to establish a nonlinear model. To efficiently analyze and discuss the model calibration methods, this study generally assumed the human body or segment can be approximately simulated as a linear system for each given test condition, although the inverse dynamic approach is generally applicable to any linear and nonlinear system [7,9,13,14]. Six models found in the literature are shown in Fig.…”
Section: Basic Theory and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting the expression for kinetic (6) and potential (8) energy, and the expression for the dissipation function (13) into Lagrange's equations of the second kind (5), one obtains a system of six homogenous differential equations of the oscillating system:…”
Section: Dissipation Functionmentioning
confidence: 99%
“…Previous research in the area has been related to the development of mathematical models for the analysis of the static stability of hydraulic excavators [1][2][3][4]. However, the studies have shown that hydraulic excavators (and other hydraulic mobile machines) act like dynamic oscillating systems during their cyclic operation [5][6][7] where actuators (hydraulic motors and hydraulic cylinders) of the excavator drive mechanisms appear as extremely elastically dampened system members in the shape of hydraulic springs. They occur due to the compressibility of oil in the actuator displacement and ducts of the excavator hydrostatic drive system.…”
Section: Introductionmentioning
confidence: 99%